(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of oral ferrous sulphate and intravenous ferrous sucrose in postpartum iron deficiency anemia. Study Design: Randomized control experimental study. Place and Duration of Study: This study was conducted at the Postoperative and postnatal wards of sheikh Zaid women hospital Larkana from 1ST April 2016 to 30 September 2016. Materials and Methods: Sixty cases of postpartum iron deficiency anemia were collected for this study and they were divided in two groups of 30 each. Group A was treated by intravenous ferrous sucrose 200mg given on day 2 and 4 of delivery (two doses only). Group B patients were received oral ferrous sulphate 200mg daily for 6 weeks. The follow up was done at day 15 and 40 postpartum in each group in term of increase hemoglobin and ferritin level. Results: The mean Hb within 24-48 hours of delivery was 8.14±0.48gm/dl in group A and 8.73±0.66gm/dl in group B. The mean serum ferritin level was 11.37±1.67mcg/L in group A and 12.43±1.48mcg/L in group B. In group A, the mean Hb after 15 days follow up was 11.29±1.32gm/dl and in group B 9.94±0.55gm/dl and in group A, the mean serum ferritin level was 34.69±3.27mcg/L and in group B 14.73±0.98mcg/L. In group A, the mean Hb after 40 days follow up was 12.89±0.79 gm/dl and in group B was 11.40±0.39 gm/dl and in group A, the mean serum ferritin level was 46.18±4.05 mcg/L and in group B was 17.47±1.30 mcg/L. Conclusion: Intravenous iron sucrose therapy increases the Hb level as well as serum ferritin level more rapidly than oral ferrous sulphate in women with postpartum anemia deficiency anemia.